The Impact of The World Trade Organization (WTO) Import Quota Policy on Indonesian Rice Import from Thailand in 2015-2020 - Rokhaniyah, Hesti; Rahayu, Dini Septyana; Amalia, Novi Rizka; Saputro, Muhammad Ilham (Dauliyah: Journal of Islam and International Affairs, 2023)
This study aims at analyzing the impact of policies regulated by the WTO on Indonesian rice imports from Thailand for the 2015-2020 period. The import quota policy is one of the policy instruments used by the Indonesian government in realizing sovereign and independent food. This study useda qualitative descriptive method with data collection techniques from books, journals, and data obtained from government agencies. Meanwhile, the analysis in this study employed deductive analysis by explaining general data to form specific views; thus, those data could be drawn into the conclusions. The results of this study indicate that the impact of the import quota policy seen from the aspect of international trade on Indonesian rice imports was in the form of expanding the global market and continuing bilateral relations between Indonesia and Thailand in the rice sector through an agreement to import 1 million tons of rice. While the impact of the international regime aspect with its three main components namely output, outcome, and impact shows that: the formation of agreements in the agricultural sector as contained in the Agreement on Agriculture (AoA) approved by the WTO, the existence of ratification of government policies through various regulations at the Presidential Decree, Presidential Instruction and Ministerial Regulations to enforce the liberalization of trade in goods including various necessities, such as rice and other agricultural products, and the implementation of a policy of limiting import quotas from 2015 to 2020.